2018
DOI: 10.1002/ccd.27596
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HAS‐BLED score to predict trans femoral transcatheter aortic valve replacement outcomes

Abstract: HAS-BLED score could predict the risk of severe bleeding and mortality in patients who underwent TF-TAVR independent of the presence of atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This study demonstrates that the risk of CVE following TAVR is associated with (A) calcification burden of the device landing zone, namely, the RCC as a surrogate parameter of the aortic valve, LVOT, and ascending aorta calcification burden; (B) higher mechanical forces during the implantation process, caused by larger aortic angulation, snaring, and residual aortic regurgitation; and (C) lack of post-procedural dual antithrombotic or anticoagulation treatment. Our developed risk model was superior to both established risk scores for outcome prediction (EuroSCORE II and STS score) mentioned in the current guidelines [1], as well as the risk scores examined for CVE prediction after TAVR in previous studies (CHA 2 DS 2 -VASc score and HAS-BLED score) [9,10]. Nevertheless, the reliability of CVE prediction is limited due to the infrequency of this event.…”
Section: Discussionmentioning
confidence: 74%
“…This study demonstrates that the risk of CVE following TAVR is associated with (A) calcification burden of the device landing zone, namely, the RCC as a surrogate parameter of the aortic valve, LVOT, and ascending aorta calcification burden; (B) higher mechanical forces during the implantation process, caused by larger aortic angulation, snaring, and residual aortic regurgitation; and (C) lack of post-procedural dual antithrombotic or anticoagulation treatment. Our developed risk model was superior to both established risk scores for outcome prediction (EuroSCORE II and STS score) mentioned in the current guidelines [1], as well as the risk scores examined for CVE prediction after TAVR in previous studies (CHA 2 DS 2 -VASc score and HAS-BLED score) [9,10]. Nevertheless, the reliability of CVE prediction is limited due to the infrequency of this event.…”
Section: Discussionmentioning
confidence: 74%
“…In the pivotal trials for patients with low or intermediate surgical risks, the incidences of serious bleeding events for 1 year ranged between 3.2% and 15.2% 17–19. Moreover, that was 18.2% in a prospective registry20 and the incidence of bleeding events was low in this study. Bleeding events often include the drop of haemoglobin in the endpoint definition of TAVR trials, but it was not included in this study, because whether it is obvious that bleeding was unknown in this registry data.…”
Section: Discussionmentioning
confidence: 52%
“…The European guidelines do indicate that SAPT may be considered after TAVR in patients at high bleeding risk (class IIb; level of evidence: C) . While no specific threshold is recommended, a HAS-BLED score of 4 points or more was considered high bleeding risk in 1 study, whereas a HAS-BLED score of 3 points or more is generally used to indicate high bleeding risk in the context of AF or coronary interventions. In clinical practice, the Society for Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy Registry reported that of 16 694 patients, 13 546 (81.1%) with no indication for OACs were discharged while taking DAPT after TAVR between 2011 and 2016, whereas 3148 patients (18.9%) were while taking SAPT, with significant variation among hospitals (data not provided) .…”
Section: Antithrombotic Therapy Studies In Tavrmentioning
confidence: 99%